2016
DOI: 10.1002/soej.12145
|View full text |Cite
|
Sign up to set email alerts
|

Information Effects in Uniform Price Multi-Unit Dutch Auctions

Abstract: We design a multi-unit descending-price (Dutch) auction mechanism that has applications for resource allocation and pricing problems. We address specific auction design choices by theoretically and experimentally determining optimal information disclosure along two dimensions. Bidders are either informed of the number of bidders in the auction, or know that it is one of two possible sizes; they also either know the number of units remaining for sale or are unaware of how many units have been taken by other bid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…• Speculators do not make profits in first-price/Dutch auctions [GT05] • If the numbers of bidders is large, the Dutch auction produces more revenue than a first-price auction [Mie13] • The most efficient and largest revenue outcome occurs when bidders are not provided information on either group size or units remaining [BGP16] • At fast clock speeds, revenue in the Dutch auction is significantly lower than in the sealed bid auction. When the clock is sufficiently slow, however, revenue in the Dutch auction is higher than the revenue in the sealed bid auction [KK08] The limited use of Dutch auctions in IPOs despite their potential for more fully pricing the issue is due to low underwriter compensation [RR12]: in French markets, there is a smaller degree of underpricing using auctioned IPOs than traditional IPOs [DW03].…”
Section: General Resultsmentioning
confidence: 99%
“…• Speculators do not make profits in first-price/Dutch auctions [GT05] • If the numbers of bidders is large, the Dutch auction produces more revenue than a first-price auction [Mie13] • The most efficient and largest revenue outcome occurs when bidders are not provided information on either group size or units remaining [BGP16] • At fast clock speeds, revenue in the Dutch auction is significantly lower than in the sealed bid auction. When the clock is sufficiently slow, however, revenue in the Dutch auction is higher than the revenue in the sealed bid auction [KK08] The limited use of Dutch auctions in IPOs despite their potential for more fully pricing the issue is due to low underwriter compensation [RR12]: in French markets, there is a smaller degree of underpricing using auctioned IPOs than traditional IPOs [DW03].…”
Section: General Resultsmentioning
confidence: 99%
“…The first to bid identifies the number of items they wish to purchase at that price, and the auction continues with the remaining items till all are sold (Mochón et al 2015). Buchanan et al (2016) observed a reduction in bid prices during multi-unit Dutch auctions when there was greater information available to bidders regarding their competitors, such as the number of participating bidders or the total remaining items, compared to when there was no information available to participants.…”
Section: Effect Of Competitors On Bidding Behaviourmentioning
confidence: 96%
“…Another important consideration in platform development was the parameter unit quantity (the amount of items presented on every sale). Research has shown information related to unit quantity can influence bidding behaviour in Dutch auctions (Buchanan et al 2016). To address this, we included a design feature that enables the unit quantity to be fixed or varied.…”
Section: Developing a Computerised Platform For Testing Dutch-auctionmentioning
confidence: 99%
“…7 Contrary to theory, they empirically find that first-price auction prices (buyer revenues) are higher, and bidding thus more competitive, in the private value case. Related, Buchanan et al (2016) find that not revealing information about group size and already sold units increases the average price in a Dutch clock auction, where n buyers can acquire at most a single unit of m goods. Both findings resemble our own result that supply uncertainty leads to a more competitive outcome.…”
Section: Related Literaturementioning
confidence: 99%
“…As emphasized byPerry and Reny (1999) orBuchanan et al (2016), the linkage principle has sometimes been (sloppily) equated with a general sentiment that increasing bidder-side information tends to increase auction revenues and efficiency by making strategic bidding more competitive.…”
mentioning
confidence: 99%